EXTH-12. INHIBITION OF EPIDERMAL GROWTH FACTOR RECEPTOR AND PLATELET-DERIVED GROWTH FACTOR RECEPTOR-ALPHA EXERTS SYNERGISTIC EFFICACY IN GLIOBLASTOMA. (12th November 2021) - Noch, Evan; Alnahhas, Iyad; Palma, Laura; Cantley, Lewis
Abstract: Epidermal growth factor receptor ( EGFR ) alterations, including amplification and activating mutations, occur in more than half of GBM cases. EGFR is located on Chr. 7, and Chr. 7 gain is one of the earliest events precipitating gliomagenesis. EGFR inhibitors, monoclonal antibodies, vaccines, and CAR-T cells have failed in GBM due to intrinsic heterogeneity and receptor tyrosine kinase (RTK) bypass pathways that mediate therapeutic resistance. New targeted therapeutic approaches to leverage synergistic combinations are desperately needed to improve GBM prognosis. Using the TCGA and other GBM databases, we previously demonstrated that PDGFRA amplification in patients with EGFR -amplified GBM carries significantly worse survival. EGFR and PDGFRA co-expression occur in more than one-third of GBM patients. The PDGFRA ligand PDGFA is also located on Chr. 7, and its expression is significantly increased with Chr. 7 gain and EGFR copy number increase. Therefore, Chr. 7 gain inherently leads to co-activation of both EGFR and PDGFRA signaling. We used patient-derived glioblastoma cells with Chr. 7 gain to test combined inhibition of EGFR and PDGFRA in vitro. We found that combined inhibition of both EGFR and PDGFRA using FDA-approved EGFR-targeted agents (Erlotinib, Gefitinib, Dacomitinib, Neratinib, and Osimertinib) and Crenolanib, respectively, leads to synergistic cytotoxicity in vitro . Inhibition of either EGFR or PDGFRA led to receptor cross-activation, and EGF and PDGF-AA-induced RTK activation was blocked by Neratinib and Crenolanib. Immunoprecipitation experiments and proximity ligation assays demonstrated that combined inhibition prevents EGFR and PDGFRA heterodimerization and pathways of therapeutic resistance. This combined inhibition led to decreased activation of downstream signaling pathways, including PI3K and MAPK. We show that combined inhibition of EGFR and PDGFRA exerts synergistic cytotoxicity in GBM and prevents resistance pathways that emerge during single-agent targeted therapy. These pathways are targetable with FDA-approved agents that could be used in patients with GBM with Chr. 7 gain.